A concise approach to tajweed - Hassan, Surul Shahbudin; Abd. Rahman, Akmal Khuzairy (IIUM, 2012)
This a study of the Science of Tajweed written in English titled Concise Approach to Tajweed. It is a study covers the debate about the science of recitation to that narrated his reading of the Prophet according Qiraat like `Asim Imam Hafs narrated by Imam Ash-flow through Syatibiah. It is recommended reading for those who learn the Quran and is an example of reading most Muslims around the world. This book has also been prepared to meet the method of writing the Koran Resam Uthmani. There are chapters in this study only the things that are important only. Its contents are just highlighting the basic things that should be known only without lengthy debate. This study is actually a result of the author after many years involved in teaching the science of recitation. In the beginning of this study is in the form of sheet notes distributed to the students during the author teaches at the International Islamic University Malaysia. The notes are arranged in order to fulfill the requirements of its international students studying in IIUM.